2007
DOI: 10.2134/jeq2007.0160
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Application Rate of Water Treatment Residual for Agronomic and Environmental Benefits

Abstract: Water treatment residuals (WTR) are useful soil amendments to control excessive soluble phosphorus (P) in soils, but indiscriminate additions can result in inadequate control or excessive immobilization of soluble P, leading to crop deficiencies. We evaluated the influence of application rates of an Al-WTR and various P-sources on plant yields, tissue P concentrations, and P uptake and attempted to identify a basis for determining WTR application rates. Bahiagrass (paspalum notatum Fluggae) was grown in a P-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…For example, Basta et al (1996) applied WTRs to soils treated with poultry manure and successfully reduced P in run-off by more than 50%. The same degree of P retention has been demonstrated in other, more recent studies (Agyin-Birikorang et al, 2007;Oladeji et al, 2007Oladeji et al, , 2008. In addition, Macks and co-workers (Macks, 1997;Macks et al, 1998) have shown that WTRs could be used to successfully remove P from agricultural waste waters.…”
Section: Introductionsupporting
confidence: 63%
“…For example, Basta et al (1996) applied WTRs to soils treated with poultry manure and successfully reduced P in run-off by more than 50%. The same degree of P retention has been demonstrated in other, more recent studies (Agyin-Birikorang et al, 2007;Oladeji et al, 2007Oladeji et al, , 2008. In addition, Macks and co-workers (Macks, 1997;Macks et al, 1998) have shown that WTRs could be used to successfully remove P from agricultural waste waters.…”
Section: Introductionsupporting
confidence: 63%
“…Meanwhile, Oladeji et al . observed no increase in Al content in Bahiagrass or ryegrass (Lolium perenne L.) from Immokalee fine sand (Alaquods) applied with DWTR43. These differences may be mainly related to the different soil properties and plants used in the tests4243.…”
Section: Discussionmentioning
confidence: 97%
“…Th e decrease in plant P content was due to P adsorption on to WTR, and Bayley et al (2008a) showed that WTR acts as the major P sink in this system. Others (Oladeji et al, 2007;Lucas et al, 1994;Elliott and Singer, 1988;Bugbee and Frink, 1985) have found reduced P content of plants grown in WTR-amended soils. Mahdy et al (2007), however, found that WTR addition at rates up to 30 g kg -1 to calcareous soils signifi cantly increased corn P shoot and root concentrations.…”
Section: Plant Tissue Chemistrymentioning
confidence: 97%